CZYNNIKI AFEKTYWNE W TEORII I BADANIACH NAD ZDOLNOŚCIAMI JĘZYKOWYMI - Biedroń, Adriana (Neofilolog, 2019)
There is much controversy surrounding the influence of affect on foreign language aptitude. In most foreign language aptitude models and tests this factor is treated marginally or it is entirely absent. In research studies, much attention is devoted to individual factors defined in the context of positive psychology, but their relationships with cognitive factors are rarely analyzed. This paper is an attempt to present the role of factors other than cognitive in foreign language aptitude theory and research, selected reasons for their weak position, as well as pedagogical implications and suggestions for further research.